Experimental research of the software complex to attack the linguistic stegosystem - Тарасенко, Ярослав Володимирович (Ukrainian Information Security Research Journal, 2018)
Steganography, in particular linguistic steganography, acquires new forms due to the use of computer technologies and the Internet as well as the growing influence of information technologies on all spheres of human life. Modern methods of the textual information steganalysis are not intended for the purpose of efficiently use to attack the linguistic stegosystem, and the systems of automated text summarization do not take into account the possibility of steganographic techniques usage. The author implemented and pre-tested the software complex to attack the linguistic stegosystem on the basis of the method of the textual data compression for linguistic steganography. So, the final experimental research of the developed method implementation`s effectiveness is relevant. Therefore, the preliminary obtained data are specified in the work and the final conclusions about the effectiveness of the software complex and, accordingly, the method are presented. The experiment’s method based on the functional testing has been chosen and an additional module for evaluating experimental results has been developed. Thus, the preliminary results and conclusions were confirmed and the identified defects were corrected. The hypothesis about the stegomessage hidden in the text removal possibility by almost one hundred percent without loss of the semantic structure and the validity of assumptions about the impossibility of recovering the stegomessage after the modification of the text by the developed software complex is proved. As a result of comparison with analogues, it was proved that even though the developed system of steganalysis has shown a worse efficiency, it covers much wider range of investigated elements, which provides a significantly higher efficiency of the attack based on compression. The efficiency of using the developed method and software complex for steganography problems is proved.